2015
DOI: 10.1007/s00380-015-0657-1
|View full text |Cite
|
Sign up to set email alerts
|

Patients with left ventricular ejection fraction greater than 58 % have fewer incidences of future acute decompensated heart failure admission and all-cause mortality

Abstract: Based on our previous observation, inertia stress (IS) of late systolic aortic flow was often observed in left ventricles with relatively higher left ventricular (LV) ejection fraction (EF). Most left ventricles with relatively lower LVEF did not have IS. Accordingly, lack of IS may correlate with LV diastolic dysfunction through the loss of LV elastic recoil and may contribute to the pathogenesis of heart failure (HF) and reduced survival. We enrolled 144 consecutive patients that underwent cardiac catheteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 34 publications
2
31
2
Order By: Relevance
“…The loss of IFLAF is highly associated with the impairment of LV relaxation because of a lack of elastic recoil at the very early phase of diastole 7, 17, 20. We also demonstrated previously that LVEF < 58% could significantly predict the loss of inertia force in patients with preserved LVEF 8. In addition, several other studies that used Doppler echocardiography or cardiac magnetic resonance have reported the impairment of systolic function in patients with LVEF levels that are much higher than 50% (up to around 60%) of LVEF in patients with preserved LVEF 4, 5, 6, 8.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The loss of IFLAF is highly associated with the impairment of LV relaxation because of a lack of elastic recoil at the very early phase of diastole 7, 17, 20. We also demonstrated previously that LVEF < 58% could significantly predict the loss of inertia force in patients with preserved LVEF 8. In addition, several other studies that used Doppler echocardiography or cardiac magnetic resonance have reported the impairment of systolic function in patients with LVEF levels that are much higher than 50% (up to around 60%) of LVEF in patients with preserved LVEF 4, 5, 6, 8.…”
Section: Discussionsupporting
confidence: 70%
“…Goto et al . reported the importance of IFLAF as a prognostic indicator in patients with preserved LVEF 8. Furthermore, when the tightness of correlation was compared between patients with rlEF and those with rhEF, such a correlation would become significantly lower in the patients with rhEF ( r  = −0.228, P  < 0.001) compared with those with rlEF ( r  = −0.345, P  < 0.001).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…To evaluate pumping function of the left ventricle, ejection fraction is the most common parameter that is measured. 3 Ejection fraction is measured in percentage and refers to the percentage of the blood that leaves the ventricle each time the heart contracts. Ejection fraction is conventionally measured for the left ventricles and this is the reason why in most cases, Ejection Fraction commonly refers to Left Ventricular Ejection Fraction (LVEF).…”
Section: Introductionmentioning
confidence: 99%